Visualizing Energy: An AR Approach to Promoting Sustainable Consumption Habits - Zakwan, Jamilah Khairin; Hussien, Nur Syahela (Journal of Computing Technologies and Creative Content, 2025)
Energy consumption refers to the use of energy by household appliances, devices, and systems across residential, commercial, and industrial sectors. Beyond the total energy used, understanding consumption patterns is crucial in managing costs and promoting environmental sustainability. Many consumers lack awareness of how their daily energy usage impacts both expenses and the environment, leading to inefficient energy consumption, increased costs, and negative ecological consequences. This study explores the role of digital tools, particularly augmented reality (AR), in visualizing energy consumption and fostering sustainable habits. The research focuses on developing an AR-based Energy Consumption Awareness Application that provides users with interactive, real-time feedback on their energy usage. By leveraging a user-centered design approach and probability simple random sampling, this study evaluates how AR can enhance user engagement and encourage informed decision-making regarding energy efficiency. Results showed that 73.7% of participants were aware of appliance-level energy usage, 86.8% reported an increase in energy awareness after using the app, and 92.1% believed the app had the potential to influence their energy-efficient decisions. These findings support broader adoption of AR technology in energy management and present opportunities for collaboration with industry stakeholders such as Tenaga Nasional Berhad (TNB) or Suruhanjaya Tenaga.